The Politics of Race and Ethnicity in Matthew's Passion Narrative - Park, Wongi (Palgrave Macmillan US, 2019)
Intro -- Acknowledgments -- Contents -- List of Figures -- Chapter 1: Introduction -- Identifying the Problem -- A Preliminary Definition of Race and Ethnicity -- Preview of the Argument -- References -- Chapter 2: Identifying the Dominant Narrative: Non-ethnoracial Readings of Matthew 26-27 -- Introduction -- The Title in the Gospel of Matthew -- Religious-Theological Readings of the Title -- Socio-Political Readings of the Title -- Dominant Reading Strategies of Matthean Studies -- Conclusion -- References -- Chapter 3: Situating the Dominant Narrative: Deracialized Readers and Reading Locations -- Introduction -- Deracialization as White Invisibility -- Deracialized Critics -- Deracialized Criticism -- Deracialized Representations of Jesus -- Conclusion -- References -- Chapter 4: Constructing a Minoritized Approach: Racialized Readers and Reading Locations -- Introduction -- The Black and Mestizo Jesuses: Siker's Reading of Cone and Elizondo -- Deracialization as Dominantization -- The Historical and White Jesuses: My Reading of Siker -- Conclusion -- References -- Chapter 5: Proposing an Alternative Narrative: An Ethnoracial Reading of Matthew 26-27 -- Introduction -- Dominant-Minority Dialectic in Matthew 26-27 -- Minoritizing Jesus in the Judean Court -- Minoritizing Jesus in the Roman Court -- Minoritizing Jesus in the Popular Court -- Minoritizing Jesus in the Divine Court -- Conclusion -- References -- Chapter 6: Conclusion -- References -- Index.